Methods and methodologies : Aristotelian logic East and West, 500-1500 - Cameron, Margaret (Margaret Anne); Marenbon, John (Investigating medieval philosophy ;, 2011)
"Methods and Methodologies" explores two questions about studying the Aristotelian tradition of logic. The first, addressed by the chapters on methods in the first half of the book, is directly about the medieval logical commentaries, treatises and handbooks. How did medieval authors in the different traditions, Latin and Arabic, go about their work on Aristotelian logic? In particular, how did they themselves conceive the relationship between logic and other branches of philosophy and disciplines outside philosophy? The second question is about methodologies, the subject of the chap.